2012
DOI: 10.1177/1948550612469039
|View full text |Cite
|
Sign up to set email alerts
|

Familial Self as a Potent Source of Affirmation

Abstract: Does affirmation of familial self have a distinct buffering function compared to affirmation of close other (friend, partner) self or individual self? We addressed this question in an East-Asian culture (China) that places particularly high value on familial self. Familial self-affirmation (compared to other forms of self-affirmation as well as low affirmation) curtailed the mortality salience-induced intolerance to birth-control policy (Experiment 1), reduced female participants' performance detriments-due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…For example, Chinese participants show less of a self-other distinction than Westerners (Sui, Liu, & Han, 2009;Zhu, Zhang, & Han, 2007; see also Cai, Sedikides, & Jiang, 2013). Our findings complement this view.…”
Section: Codasupporting
confidence: 83%
“…For example, Chinese participants show less of a self-other distinction than Westerners (Sui, Liu, & Han, 2009;Zhu, Zhang, & Han, 2007; see also Cai, Sedikides, & Jiang, 2013). Our findings complement this view.…”
Section: Codasupporting
confidence: 83%
“…A relatively small body of work has explored the advantages of affirming other social aspects of the self, such as the relational self or “self-as-close-other” (Brewer & Gardner, 1996; Chen & Boucher, 2008), the familial self or “self-as-family-member” (Cai, Sedikides, & Jiang, 2013), and the interdependent self or culturally collectivistic self (Hoshino-Browne et al, 2005; Markus & Kitayama, 1991). For example, Hoshino-Brown et al (2005) developed an interdependent self-affirmation (participants selected a value for themselves and their families and explained why they shared the value) and an independent self-affirmation (participants selected a value and explained why it uniquely described who they were).…”
Section: Discussionmentioning
confidence: 99%
“…The self-affirmation procedure was derived from Cai et al (2013). In the self-affirmation condition, participants chose one value that they and their family cherished most from four domains (financial wealth, social network, art/creativity, and knowledge).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, self-affirmation counteracts self-depletion (Schmeichel and Vohs, 2009). Our previous research showed that self-affirmation functions similarly in China as it does in the West (Cai et al, 2013). Unlike in the West, the operative component in China is the affirmation of a familial self (writing about core values shared by oneself and his/her family) rather than the individual self (writing about personal core values; Cai et al, 2013).…”
Section: Introductionmentioning
confidence: 97%